Port-Light / Nurul Anis Nasuha Rafie ... [et al.] - Rafie, Nurul Anis Nasuha; Hilmey, Ain Sofhia; Sukeri, Nur Aishah Aqillah; Adam, Nur Hamizah; Shafie’e, Siti Syafiqa; Azhar, Nurul Aina Afiqah; Mohamad Shukor, Amirah Syadiyah (2022)
Lately, there have been a few products of torchlight. Most of the torchlights that are sold in the market are in one angle only. To improvise the version of the current torchlight that is available on the market, we add some additional functionality and features that will deliver an enormous value to customers. Now we welcome the lamps that can be used as a torchlight and table lamps, 2 in 1 package with the latest technological advances which we call a Port-Light. Our company is called BLIGHT TECH, and we produce the Port-Light which is a combination of torchlight and table lamp. Port-Light uses solar panels to gain energy and also can be rechargeable using electricity. Customers will receive this product in a box with a waterproof bag. Port-Light is made up of a few components which are the body is made of aluminium alloy, the type of light is LED, water resistance, environmentally responsible design, light and portable design, and an adjustable stand. This product contains two light sources which are a front lamp and a lower bulb. This product also has three steps less dimming options for the light mode. The target market of this product are college students, travellers, forest rangers, security guards and hikers. The college students are referring to the residents at the UiTM Seremban 3 college dorm since the students need torchlights to ensure their safety and can transform the stand into a study lamp at night. The travellers, with no limitation ages, are free to use this portable product as it is easy to use. The forest rangers are referring to the forest police that becomes a priority when carrying out missions in the jungle, and it will benefit them since it has multiple functions and is waterproof. The security guards can also use this product to make patrols and physical inspections, especially at night and very suitable with the various functions provided. Last but not least, this product will help hikers as Port-Light can be transformed to table lamps while they are camping and using solar systems to charge.